Revisión crítica de las concepciones habituales sobre el IVA - Vásquez del Rey Villaneva, Antonio (Revista de Derecho, 2019)
The legal approach to VAT has been traditionally weighed down by some economic considerations as well as by a too formalistic approach. From that perspective, VAT should not be regarded as a turnover tax, as it is usually seen in the EU environment. Moreover, for the purposes of a legal approach it is necessary to differentiate between the goal of VAT, which is to levy a tax on consumption, and the mechanism by which that result is intended. In the first case, one must not oversize the existence of some exceptions to the ordinary functioning of VAT; otherwise, there is a risk of distorting the truth as regards the justification of the tax on the ability to pay principle. Regarding specifically the tax mechanism, the most widespread notion cannot be accepted either as its excessive formalism also leads to a somehow distorted view. The chargeable eventalways involves the payment of the tax, however, both the collection from customers and the right of deduction are key elements which do not allow categorizing VAT´s legal structure within the traditional tax law categories.